2023
DOI: 10.1021/acs.chemrev.3c00402
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Phase Engineering in Heterogeneous Catalysis

Jian-Wen Zhao,
Hong-Yue Wang,
Li Feng
et al.

Abstract: The performance of a chemical reaction is critically dependent on the electronic and/or geometric structures of a material in heterogeneous catalysis. Over the past century, the Sabatier principle has already provided a conceptual framework for optimal catalyst design by adjusting the electronic structure of the catalytic material via a change in composition. Beyond composition, it is essential to recognize that the geometric atomic structures of a catalyst, encompassing terraces, edges, steps, kinks, and corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 339 publications
0
4
0
Order By: Relevance
“…Additionally, amorphous phase materials are also vital metastable-phase materials, exhibiting the characteristics of long-range disordered arrangements with no close-packed plane, e.g., amorphous IrO 2 and RuO 2 . , However, the preparation of metastable-phase materials still poses significant challenges due to their inherent thermodynamic instability. Furthermore, the stringent conditions required for selective growth of metastable-phase metal oxides present a formidable obstacle, which greatly stimulates the research enthusiasm in developing facile synthetic methods. , …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, amorphous phase materials are also vital metastable-phase materials, exhibiting the characteristics of long-range disordered arrangements with no close-packed plane, e.g., amorphous IrO 2 and RuO 2 . , However, the preparation of metastable-phase materials still poses significant challenges due to their inherent thermodynamic instability. Furthermore, the stringent conditions required for selective growth of metastable-phase metal oxides present a formidable obstacle, which greatly stimulates the research enthusiasm in developing facile synthetic methods. , …”
Section: Introductionmentioning
confidence: 99%
“…Crystal phase engineering of nanomaterials stands as a crucial aspect of materials science that presents versatile applications in various fields such as semiconductors, magnetic materials, energy storage, optical and photonic materials, and catalysis. The application of crystal phase engineering has held particular significance in recent years, notably in catalysis, where it has garnered substantial attention for enhancement of the performance of nanoparticle (NP) catalysts. A number of investigations have shown that crystal-phase engineering can be a promising approach to modulate the performance of catalysts by alteration of the electronic and geometric structures of catalyst surfaces . Cobalt catalysts are increasingly regarded as promising alternatives to noble metallic catalysts due to their efficiency, environmental friendliness, and high abundance on Earth .…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations have shown that crystal-phase engineering can be a promising approach to modulate the performance of catalysts by alteration of the electronic and geometric structures of catalyst surfaces. 6 Cobalt catalysts are increasingly regarded as promising alternatives to noble metallic catalysts due to their efficiency, environmental friendliness, and high abundance on Earth. 21 These catalysts have gained prominence, particularly in the Fischer–Tropsch synthesis within industrial applications, due to their commendable intrinsic activity at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) layered materials have become a hotspot in the field of materials science owing to their physical and chemical properties . Among them, a subset of 2D materials exhibit phase transitions triggered by environmental factors. , Transition metal dichalcogenides (TMDs) stand out in this subset, offering atomic-scale thickness, direct bandgaps, significant spin–orbit coupling, and notable electronic and mechanical properties.…”
mentioning
confidence: 99%